Sign L - The Development of Sign Language System for Primary School Student - Mohammed Edries, Alyaa Al'adwiyah; RAMLI, AZIZUL AZHAR (Applied Information Technology And Computer Science, 2023)
Sign language is a body language that communicates with people through hand gestures. Sign language is frequently used to communicate with deaf or hard-of-hearing people, whereas deafness is a condition in which the ability to hear sounds is lost. However, there are several problems that deaf people face in daily life where they must understand people speak. Over time, deaf people try to read my lips and gestures to understand words when people speak naturally. Therefore, this project aims to develop and propose a web system that ordinary people will use by learning a simple virtual sign language. In addition, the ADDIE model is the best methodology for applying sign language development in primary school. This project allows people to learn basic sign language using digital platform learning approaches. In summary, to secure education, society should have a new learning alternative to support awareness of communication with deaf people.